Anti-Inflammatory And Immunomodulatory Effects Of Green Tea Extract (Gte) - RICHA PATEL,; PRAMOD KUMAR GUPTA, (International Journal of Pharma and Bio Sciences, 2011)
In recent years, there is growing interest in the fact that immune functions can be modulated by plant polyphenols. Immune system provides us with the specific mechanisms to resist against a particular pathogen or foreign substances and takes part in the preservation of normal cells. In the present study, the effect of green tea extracts (GTE) on modulation of immune responses in RAW 264.7 cell lines was studied. We report here that, the production of proinflammatory cytokines such as tumor necrosis factor alpha (TNFα), interleukin 1β (IL-1β), and interleukin 6 (IL-6) by RAW 264.7 cells pre-stimulated with lipopolysaccharide (LPS)<s>,</s> was inhibited by treatment with GTE. GTE treatment up regulated the secretion of anti-inflammatory cytokine TGF-β. GTE also inhibited lipopolysaccharide (LPS)-induced NO production in RAW 264.7 cells. These results demonstrate the anti-inflammatory and immunomodulatory properties of GTE on cells of innate immune system.